The Influence of Good Corporate Governance Mechanisms, Leverage, and Company Size on the Audit Quality of Banking Companies Listed on the Indonesian Stock Exchange in 2021-2022 - Luvika*, Avi Davyu; Wafa, Zaenal (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
A This research aims to determine the influence of good corporate governance mechanisms, leverage, and company size on the audit quality of banking companies listed on the Indonesia Stock Exchange (BEI) in 2021-2022. Data collection techniques using literature study and documentation. The population in this research is all banking companies registered on the IDX for the 2021-2022 period, namely 44 companies. Data analysis using descriptive statistical tests, classical assumption tests (normality, multicollinearity, heteroscedasticity and autocorrelation), logistic regression tests and hypothesis tests (t test). The research results show that the size of the board of directors, leverage and company size have an effect on audit quality, while the size of the audit committee has no effect on audit quality. This indicates that the larger the size of the Board of Directors, the better the supervisory function. Thus, we will choose the Big Four KAP to guarantee audit quality. The smaller the company's leverage, the greater the company's opportunity to use Big Four KAP. Company size influences the company's decision to use Big Four KAP, while the size of the audit committee does not influence the company's decision to use Big Four or Non-Big Four KAP.